Анализ технологических процессов штамповки ступенчатых, коленчатых и эксцентриковых валов высадкой со сдвигом - Зальвовский, О. Ю.; Кузьменко, Виктор Иванович (НТУ "ХПИ", 2014)
Работа посвящена анализу процессов штамповки: ступенчатых валов с учетом потери устойчивости высаживаемой заготовки, заготовок коленчатых валов штамповкой в открытых штампах, а также путем использования прогрессивных методов обработки металлов давлением. Разработана методика экспериментального анализа и конструкция штампа для исследования процесса Намечены пути получения заготовки эксцентрикового вала тормозной системы автотракторной техники с использованием операций высадки со сдвигом (изгибом)

This article is dedicated to analysis of the processes of punching of: - the stepped shafts in consideration of buckling planted workpiece; - workpieces of crankshafts by punching in open dies(iuiH open press tools); - and also by using of advanced methods of metal forming. Design and operational features of the crankshaft and the eccentric shaft are studied. It's stipulated the using of the cold heading method with a shift as the most suitable and rational for the production of parts such as the eccentric shaft. Ways of getting the workpiece of eccentric shaft of brake system of automobile and tractor's equipment by using cold heading operations with a shift (bending). Setting task is to explore this process to obtain energy and power parameters
Process analysis of stepwise cranked and eccentric shafts upset with shift stamping
Keywords: горячая объемная штамповка; холодная объемная штамповка; качество штамповок; метод конечных элементов; макроструктура; stepped shaft; crank shaft; eccentric shaft; hot forging; cold heading; macrostructure